Chloris gayana Kunth under different defoliation regimes : morphogenesis, sward structure and leaf area index - Ruolo, María Soledad (2019)
Fil: Ruolo, María Soledad. Instituto Nacional de Tecnología Agropecuaria (INTA). Centro Regional Córdoba. Estación Experimental Agropecuaria Manfredi (EEA Manfredi). Córdoba, Argentina.